INTERNATIONAL PROCESS OF STUDENTS OF HIGHER EDUCATION INSTITUTIONS AND EDUCATIONAL RESULTS - Doniyorova Shoxista Shodiyarovna (Galaxy International Interdisciplinary Research Journal, 2021)
This article defines the way in which higher education institutions today co-operate with international student education and exchange programs to be ranked in the world. the focus is on the learning outcomes of students through internationalization, how international experiences, global perspectives on their discipline and intercultural abilities can benefit students in the long run by enhancing their personal and employment skills, based on international experience the need to internationalize curricula and the development of their tools for home-based study abroad without going abroad.